The surface-enhanced Raman scattering of all-inorganic perovskite quantum dots of CsPbBr3 encapsulated in a ZIF-8 metal–organic framework. (8th October 2020) - Xin, Mingyang; Fu, Yuzhou; Zhou, Yue; Han, Junhe; Mao, Yanli; Li, Mengjia; Liu, Junhui; Huang, Mingju
Abstract : We used a one-pot method to synthesize CsPbBr3 @ZIF-8 and found that it has strong surface-enhanced Raman scattering performance and stability at room temperature. Abstract : In this study, composites composed of all-inorganic perovskite quantum dots (QDs) of CsPbBr3 encapsulated in a metal–organic framework of ZIF-8 (CsPbBr3 @ZIF-8) were prepared using an in situ chemical reduction method. For the first time, the CsPbBr3 @ZIF-8 composites were used for surface-enhanced Raman scattering (SERS). The CsPbBr3 @ZIF-8 composites remained effective and emitted normal luminescence under UV illumination after 200 days of storage at room temperature, indicating that they were able to overcome the instability of perovskite QDs at room temperature and that they can be stored for long-term use. The enhancement factor value is 1.17 × 10 5 . The adsorption behavior of 4-mercaptopyridine (4-MPY) on the CsPbBr3 @ZIF-8 composites was studied using typical SERS spectral bands, and these were contrasted with the SERS spectra on silver films. The enhancement mechanism is attributed to a charge transfer contribution. The results indicate that CsPbBr3 @ZIF-8 composites have potential application in SERS detection.